PENGARUH PEMBELAJARAN BERDIFERENSIASI DALAM MODEL PROJECT BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS IV SD NEGERI 2 SUMBERAGUNG KABUPATEN TULUNGAGUNG - Annisa Testi Rahmawati; Sulastri Rini Rindrayani (CV. ADIBA AISHA AMIRA, 2025)
This study aims to describe the influence of differentiated learning in the project-based learning model on the critical thinking abilities of the fourth-grade students at SDN 2 Sumberagung. This research method employs a quasi-experimental approach. The population of this study consists of all 30 students of the fourth grade at SDN 2 Sumberagung . The sampling technique used is saturated sampling. Therefore, the sample consists of 30 students. Data collection techniques involve using a test, that is, test questions becoming the research instrument. The hypothesis analysis requirements consist of tests for data normality and homogeneity, and the data analysis technique employs the t- test. The results of the normality test show that the post-test scores for both the control class and the experimental class are normally distributed, with a significance value of 0.097 > 0.05 for the experiment class and 0.148 > 0.05 for the control class. Meanwhile, the homogeneity test results show that the probability value of 0.703 > 0.05 indicates that both groups have homogeneous variances. Furthermore, the results of the average difference test between the post-test scores of the control class and the experimental class indicate that the average post-test critical thinking abilities of students in the experiment class are higher than that of the control class, namely 78.87 > 65.40. The independent t-test result is also significant, with 0.001 < 0.005. Accordingly, in conclusion, differentiated learning in the project-based learning model influences the critical thinking abilities of the fourth-grade students at SDN 2 Sumberagung